Community organizing and community building for health and welfare - Minkler, Meredith (Rutgers University Press, 2012)
The third edition of Community Organizing and Community Building for Healthand Welfare provides new and more established ways to approach community building and organizing, from collaborating with communities on assessment and issue selection to using the power of coalition building, media advocacy, and social media to enhance the effectiveness of such work. With a strong emphasis on cultural relevance and humility, this collection offers a wealth of case studies in areas ranging from childhood obesity to immigrant worker rights to health care reform. A "tool kit" of appendixes includes guidelines for assessing coalition effectiveness, exercises for critical reflection on our own power and privilege, and training tools such as "policy bingo." From former organizer and now President Barack Obama to academics and professionals in the fields of public health, social work, urban planning, and community psychology, the book offers a comprehensive vision and on-the-ground examples of the many ways community building and organizing can help us address some of the most intractable health and social problems of our times
"Edited by Meredith Minkler"--Cover
Keywords: Health promotion.; Community health services -- Citizen participation.; Community organization.; Community development.; Culture.; Information storage and retrieval systems.; Social ecology.; Sociology.; Ethnology.; Social sciences.; Anthropology.; Health education.; Consumers' leagues.; National health services.; Cultural pluralism.; Non-governmental organizations.; Health planning.; Medical care.; Culture; Regional Health Planning; Preventive Health Services; Education, Nonprofessional; Information Systems; Social Environment; Sociology; Health Care Economics and Organizations; Health Care Facilities, Manpower, and Services; Anthropology, Cultural; Medical Informatics Applications; Medical Informatics; Social Sciences; Delivery of Health Care; Anthropology; Anthropology, Education, Sociology and Social Phenomena; Information Science; Health Education; Community Health Planning; Consumer Organizations; Health Services; Community Networks; Cultural Diversity; Community Health Services; Organizations; Education; Health Planning; Health Promotion; Patient Care; Promotion de la santé.; Services communautaires de santé -- Participation des citoyens.; Organisation communautaire.; Systèmes d'information.; Écologie sociale.; Sociologie.; Ethnologie.; Médecine -- Informatique.; Sciences sociales.; Prestation de soins.; Anthropologie.; Éducation sanitaire.; Services communautaires de santé -- Planification.; Consommateurs -- Associations.; Services de santé.; Diversité culturelle.; Organisations non gouvernementales.; Santé publique -- Planification.; Développement communautaire.; Soins médicaux.; community organizations.; culture note.; human ecology.; sociology.; social sciences.; anthropology.; community development.; culture (concept); HEALTH & FITNESS -- Diseases -- General.; HEALTH & FITNESS -- Health Care Issues.; MEDICAL -- Diseases.; MEDICAL -- Health Care Delivery.; MEDICAL -- Health Policy.; MEDICAL -- Public Health.; SOCIAL SCIENCE -- Disease & Health Issues.; Social sciences; Social ecology; Non-governmental organizations; National health services; Medical care; Information storage and retrieval systems; Health planning; Health education; Ethnology; Cultural pluralism; Consumers' leagues; Community development; Community health services -- Citizen participation; Community organization; Health promotion